On the other side of the rabbit proof fence: decolonizing social work education - a framework for change. - Moss, Michelle; Rowen, Roslyn; Lee, Anthony Duwun (Social Work Education, 2024)
The push to improve Indigenous student retention and completion rates in higher education programs is a strategic goal across Australian universities. Similarly, the notion of decolonizing education to allow for a more culturally relevant educational experience is being discussed in university curricula development. In this article, we highlight challenges within the current neoliberal political context influencing a decolonized approached to higher education. We will draw on experiences from a case study of a creative therapy course situated within a Social Work program at a regional university. A team of Indigenous and non-Indigenous researchers will propose a framework for navigating pedagogical and administrative challenges to design a course that serves as a powerful tool to advocate for changes in higher education and social work systems. We suggest that this framework can be used to build valuable connections across Indigenous and Western knowledge systems and promote truth-telling in the social work context. Finally, we argue that our framework for decolonising education is inter-disciplinary and a useful tool in helping staff and students take back their knowledge from colonial power structures. In order to decolonise social work education, we need to deconstruct the whiteness embedded in pedagogy, theory and social work practice itself. We need to work in true partnership with Indigenous knowledge holders and community members to co-create new knowledge. This framework can be used to build valuable authentic connections across Indigenous and Western knowledge systems and promote truth-telling in the social work context. This framework works to both challenge current social work curricula in Australia and attract and retain Indigenous students in social work education, which arguably would help to ensure culturally relevant practice with and by Indigenous people.